(untitled) (ModaPalavra e-periódico, 2022)
Brazil is a strong representative of world production in the textile sector. The fashion industry has economic benefits for the country, however it is responsible for negative impacts on the environment. In the search for sustainable alternatives, concepts and techniques emerge that aim to mitigate the impacts caused by the growing demand, including zero waste disposal. Fashion illustration is an area of ​​fashion that has gained greater visibility, and presents concepts, meanings and symbologies through graphics. This article approaches fashion illustration as a way to disseminate reflections on the zero disposal of textile waste. Thus, it presents illustrations that give new meaning to waste, inserting in its graphic composition textile elements arising from the construction of fashion artifacts. Therefore, the illustrations can be explored through reflective symbologies providing contributions to a cleaner and more sustainable fashion.